Formulation of metoclopramide HCl gastroretentive film and in vitro- in silico prediction using Gastroplus® PBPK software - Dalia Safaa Hamdi; Masar Basim Mohsin Mohamed (Elsevier, 2022)
The new trends in pharmaceutical studies focus on targeting drug delivery and computer software that help in the body environment simulation, such as Gastroplus® software. The interest of this study is to prepare a gastroretentive film of metoclopramide HCl (MTC) that was followed by applying the in silico approach to estimate the in vivo prepared formulations. The films were prepared from HPMC E5 and sodium alginate polymers as primary polymers with the aid of secondary polymers. The sodium alginate high proportions films showed instant and long floating duration reaching 24 h but with variable folding endurance. Moreover, sodium alginate films with their secondary polymers carbopol and HPMC E5 slowed the release of MTC. The floating and slow-release patterns assessed the gastroretentive properties of sodium alginate films and were further examined by a mucoadhesive study that guaranteed mucosal adhesion, and the film's FESEM images showed similar top morphology, but different side view structures. Last, the pharmacokinetic profile of selected films that approached the gastroretentive properties was in silico predicted depending on in vitro release study and floating duration employing the physiological-based pharmacokinetic model in Gastroplus® software. The model determines this prediction found successfully of intravenous and immediate oral release tablets (10 and 30 mg) of MTC. The simulation showed a high amount of MTC retained for long periods in the stomach to Sod.Alginate-3, Sod.Alginate-8, and Sod.Alginate-10 films (films of secondary polymers carbopol and HPMC E5) aid in reaching the optimum site of absorption jejunum 1 due to the slow MTC release.